Indicadores de desempenho para núcleos de inovação tecnológica a partir de experiências nacionais e internacionais - Bueno, Alexandre (Universidade Federal de São Carlos, 2016)
The use of performance indicators can help in decision-making, the definition of strategic actions in the planning, scenario display (current and future) and the results of operations of Technological Innovation Nucleus. This study aims to define a set of performance indicators for the management of technology transfer offices in Brazil, to evaluate, monitor the development and evolution of their actions and accomplishments. Therefore, there was a review of literature on the subject and access to and knowledge of international practices of intellectual property management and technology transfer in universities , which allowed consideration of performance indicators found so far, and the identification other new again featured and updated based on the literature. Were subsequently validated by experts (researchers with publications in the field and qualified professionals who work directly in the management of the NIT) and then there was the application of performance indicators in Brazilian universities (case studies), with reference (for obtaining data) 2015 (alone) and accumulated in the last five years (2011-2015). The importance of the issue is justified by the possibility of using them to understand, assess and monitor the evolution of the university technology transfer process for the company. The study may have great value to understand the actions taken by the NIT, contribute to the formulation of public policies (internal and universities), with the creation of a favorable environment for synergy and cooperation with business, and finally as a process accountability to society (demonstrating the achievements of technological innovation nucleus). In the search results include of performance indicators that can be used by Brazilian universities, the results achieved by each NIT and comparison among them.
Keywords: Núcleos de inovação tecnológica; Indicadores de desempenho; Transferência de tecnologia; Propriedade intelectual; Technological innovation nucleus; Performance indicators; Technology transfer; Intellectual property; ENGENHARIAS::ENGENHARIA DE PRODUCAO